Real-Time PCR Assays for Rapid Identification of Common Aphanomyces astaci Genotypes - Di Domenico, Marco; Curini, Valentina; Caprioli, Riccardo; Giansante, Carla; Mrugała, Agata; Mojžišová, Michaela; Cammà, Cesare; Petrusek, Adam (Frontiers in Ecology and Evolution, 2021)
The oomycete Aphanomyces astaci is the etiologic agent of crayfish plague, a disease that has seriously impacted the populations of European native crayfish species. The introduction of non-indigenous crayfish of North American origin and their wide distribution across Europe have largely contributed to spread of crayfish plague in areas populated by indigenous crayfish. Tracking A. astaci genotypes may thus be a useful tool for investigating the natural history of crayfish plague in its European range, as well as the sources and introduction pathways of the pathogen. In this study, we describe the development of real-time PCR TaqMan assays aiming to distinguish the five genotype groups of A. astaci (A–E) previously defined by their distinct RAPD patterns. The method was evaluated using DNA extracts from pure A. astaci cultures representing the known genotype groups, and from A. astaci-positive crayfish clinical samples collected mostly during crayfish plague outbreaks that recently occurred in Central Italy and Czechia. The assays do not cross-react with each other, and those targeting genotype groups A, B, D, and E seem sufficiently specific to genotype the pathogen from infected crayfish in the areas invaded by A. astaci (particularly Europe). The unusual A. astaci genotype “SSR-Up” documented from crayfish plague outbreaks in Czechia and chronically infected Pontastacus leptodactylus in the Danube is detected by the group B real-time PCR. The assay originally developed to detect group C (one not yet documented from crayfish plague outbreaks) showed cross-reactivity with Aphanomyces fennicus; the A. astaci genotype “rust1” described in the United States from Faxonius rusticus is detected by that assay as well. Analyses of additional markers (such as sequencing of the nuclear internal transcribed spacer or mitochondrial ribosomal subunits) may complement such cases when the real-time PCR-based genotyping is not conclusive. Despite some limitations, the method is a robust tool for fast genotyping of A. astaci genotype groups common in Europe, both during crayfish plague outbreaks and in latent infections.